Northrop Frye on Shakespeare - Frye, Northrop (New Haven ; London : Yale University Press, 1986)
Offers fresh insights into ten of Shakespeare's most popular plays, relating each of these works to others and discussing many of the central elements of Shakespearean drama
The tempest
Keywords: engleska književnost; književna kritika; Shakespeare, William - interpretacije